Boron Nitride Nanotubes Versus Carbon Nanotubes: A Thermal Stability and Oxidation Behavior Study - Kostoglou, Nikolaos; Tampaxis, Christos; Charalambopoulou, Georgia Ch; Constantinides, Georgios; Ryzhkov, Vladislav; Doumanidis, Charalabos; Matovic, Branko; Mitterer, Christian; Rebholz, Claus (My University, 2020)
Nanotubes made of boron nitride (BN) and carbon have attracted considerable attention within the literature due to their unique mechanical, electrical and thermal properties. In this work, BN and carbon nanotubes, exhibiting high purity (>99%) and similar surface areas (~200 m2/g), were systematically investigated for their thermal stability and oxidation behavior by combining thermal gravimetric analysis and differential scanning calorimetry methods at temperatures of up to ~1300 °C under a synthetic air flow environment. The BN nanotubes showed a good resistance to oxidation up to ~900 °C and fully transformed to boron oxide up to ~1100 °C, while the carbon nanotubes were stable up to ~450 °C and almost completely combusted up to ~800 °C. The different oxidation mechanisms are attributed to the different chemical nature of the two types of nanotubes.
Keywords: Boron nitride nanotubes; Carbon nanotubes; Oxidation resistance; Purity; Thermal stability